Can Customary Law Deliver Justice? Resolving Kahoba’karah (Out-of-Wedlock Pregnancy) and Kikono (Adultery) in Enggano District - Dwi Putri Lestarika; Edra Satmaidi; Linda Rahma Wati; Mohd Zhafran Abd Majiid; Carlos Luthumbu (Universitas Negeri Semarang, 2025)
The recognition of customary law in the 1945 Constitution of Indonesia serves as a foundational principle for resolving customary violations in Enggano Island, located in the North Bengkulu Regency, Bengkulu Province. This recognition facilitates the restoration of social balance within the community, ensuring both security and order. Among the most prevalent customary violations in Enggano are Kahoba’karah (out-of-wedlock pregnancy) and Kikono (adultery). These violations are addressed through local customary processes, which are deeply rooted in the values of local wisdom. This study aims to describe and analyze the role of customary law in resolving these cases on Enggano Island, exploring how local wisdom is applied in the conflict resolution process. Employing an empirical legal research methodology, the study utilizes both primary and secondary data, analyzed qualitatively. The findings indicate that the existence and application of customary law in Enggano are reinforced by various legislative measures, from Emergency Law No. 1 of 1951 to amendments in the 1945 Constitution, alongside specific customary regulations enacted by the indigenous community. The resolution process typically involves several stages, including the formal recognition of the violation, customary ceremonies, and the imposition of customary sanctions. In light of these findings, it is recommended that the North Bengkulu Regency Government promptly draft and ratify regional regulations recognizing and protecting the Enggano Indigenous Law Community. Additionally, the community is urged to maintain adherence to the normative values that govern social life on the island.